Black Beauty - Sewell, Anna, 1820-1878.; Kemp-Welch, Lucy, 1869-1958 (New York : Waldman & Son, 1977)
A horse in nineteenth-century England recounts his experiences with both good and bad masters.
Keywords: Horses -- Juvenile fiction; Horses -- Fiction